2017
DOI: 10.7575/aiac.ijalel.v.6n.6p.214
|View full text |Cite
|
Sign up to set email alerts
|

Apology Strategies Used by EFL Undergraduate Students in Indonesia

Abstract: Interlanguage speakers, regardless of proficiency level, often experience problems in communication due to their limited knowledge of how speech acts are commonly performed in the target language. The current study attempted to investigate the effects of English proficiency level on the apology strategy use by Indonesian EFL (English as a Foreign Language) learners from two English proficiency levels. The study employed a DCT (Discourse Completion Task) questionnaire and involved 21 A2 students and 21 B1 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
5
1
Order By: Relevance
“…These are consistent with the findings of this study which indicate a positive proficiency effect on the production of the speech act of apology. Although the current study showed that language proficiency has a positive effect on the production of the speech act of apology, in the Indonesian EFL context, Cedar (2017) has reported that English proficiency levels do not significantly influence the performance of the speech act. The findings of Farnia and Suleiman (2009), Arghamiri and Sadighi (2013), and Farashaiyan and Hua (2012) further revealed that there was no positive correlation between proficiency level and pragmatic competence.…”
Section: Jordanian Efl Learners' Proficiency and Pragmatic Productioncontrasting
confidence: 84%
See 2 more Smart Citations
“…These are consistent with the findings of this study which indicate a positive proficiency effect on the production of the speech act of apology. Although the current study showed that language proficiency has a positive effect on the production of the speech act of apology, in the Indonesian EFL context, Cedar (2017) has reported that English proficiency levels do not significantly influence the performance of the speech act. The findings of Farnia and Suleiman (2009), Arghamiri and Sadighi (2013), and Farashaiyan and Hua (2012) further revealed that there was no positive correlation between proficiency level and pragmatic competence.…”
Section: Jordanian Efl Learners' Proficiency and Pragmatic Productioncontrasting
confidence: 84%
“…There are similarities and differences between the findings of our study and those reported by previous studies (e.g., Arghamiri & Sadighi, 2013;Cedar, 2017;Farashaiyan & Hua, 2012;İstifçi, 2009;Li & Suleiman, 2017;Qorina, 2012;Rastegar & Yasami, 2014;Shardakova, 2005). Based on the results of this study, learners at advanced level of proficiency produced less-explicit strategy more than those at beginner and intermediate levels of proficiency.…”
Section: Jordanian Efl Learners' Proficiency and Pragmatic Productionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, a study revealed that EFL learners transferred their speech from Arabic into English due to their limited knowledge of the target language culture (Alharbi, 2017). However, Cedar, (2017) confirmed that the proficiency level did not impact the apology production between the EFL respondents. Further, Saleem et al (2014) revealed the similar AS used by female and male EFL learners.…”
Section: Introductionmentioning
confidence: 61%
“…Another controversial issue within ILP apologies research is the effect that language proficiency may have on the performance of certain apologies in a given L2. In this respect, some studies conclude that proficiency does not enhance the use of apologies (e.g., Cedar, 2017;Cohen & Olshtain, 1993;Mohebali & Salehi, 2016) while others have demonstrated that higher-level learners manage linguistic apologies more accurately than lower-level learners (e.g., Blum-Kulka et al, 1989;Istifçi, 2009;Qorina, 2012;Rastegar & Yasami, 2014;Turgut, 2010).…”
Section: Target Pragmatic Featuresmentioning
confidence: 99%